He migration and bubble formation in Ga stabilised delta-Pu - Robinson, Marc; Kenny, S.; Smith, R.; Storr, M. (Elsevier BV * North-Holland, 2014)
The migration and formation of He into bubbles in Ga stabilised δ-Pu has been investigated using molecular dynamics simulation. Formation energy calculations indicate that isolated He interstitial atoms are unfavourable and that it is preferential for He to reside as a substitutional atom at the expense of producing a Pu self-interstitial. Migration energy barrier calculations and on-the-fly kinetic Monte Carlo simulations support this result establishing that an interstitial He atom soon becomes substitutional, after which migration is unlikely unless assisted by local vacancies. He-vacancy cluster formation energies show that as the void size increases, a He:vacancy ratio up to 2:1 becomes energetically favourable over isolated He substitutional atoms and vacancies.